IDDF2019-ABS-0191 Initial experience of faecal microbiota transplantation with frozen stools for the treatment of recurrent or refractory clostridioides difficile infection – a retrospective review from a quaternary referral centre in hong kong. (June 2019) - Lui, Rashid; Lau, Louis; Chan, Ting-ting; Wong, Sunny; Cheung, Kitty; Li, Amy; Chin, ML; Tang, Whitney; Ching, Jessica; Lam, Kelvin; Chan, Paul; Wu, Justin; et al.
Abstract : Background: Clostridioides difficile infection (CDI) is a major cause of nosocomial infection leading to significant morbidity and mortality. Faecal microbiota transplantation (FMT) has emerged as a promising option for recurrent and refractory CDI. This study aims to assess the safety, efficacy and feasibility of FMT using frozen stools from a newly established stool biobank for the treatment of CDI in Hong Kong. Methods: We conducted a single-centre, retrospective study for all consecutive cases of recurrent/refractory CDI who had FMT with frozen stools performed from 2017 to present. Clinical demographics, outcome, and safety parameters were collected from the Clinical Management System of the Hospital Authority, Hong Kong or from the review of case notes. Results: A total of 19 patients with recurrent or refractory CDI and FMT performed using frozen stools from the CUHK stool biobank were identified [median age 70 years (interquartile range of 58.5 - 77.5 years); 68.4% males]. Almost half of the cases were in a bedridden or chair-bound state, a surrogate of a poor functional status. The majority (> 80%) of patients were hospitalized within the recent 3 months or were long-term care facility residents. FMT was delivered via feeding tube in 1 (5.3%), esophagogastroduodenoscopy (OGD) in 12 (63.2%), or colonoscopy in 6 (31.6%) of the patients. Resolution of diarrhoea without relapse within 8 weeks was achieved in 16 out of 19 patients (84.2%). The procedure was generally well tolerated with no serious adverse events attributable to FMT. The most common complication after FMT was abdominal pain (n = 3, 15.8%). Bloating was reported in 1 patient (5.3%). These results suggest that the cure rates of FMT using frozen stools for recurrent or refractory CDI were comparable with those reported in the literature with an excellent safety profile. Conclusions: We report the largest case series of FMT using frozen stools to treat refractory or recurrent CDI in Hong Kong, showing that it is a safe, efficacious and feasible intervention. Efforts should be made to raise the awareness of this important treatment, with earlier use in difficult-to-treat cases.